Emerging Trends in the Social and Behavioral Sciences 2015
DOI: 10.1002/9781118900772.etrds0138
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the Transition to Adulthood: A Diverse Pathways View

Abstract: The transition to adulthood can be considered as a status passage in the institutionalized life course, involving the assumption of new social roles, such as the completion of education, entry into the labor market, and family formation (Shanahan, 2000). It is guided by age‐related legal norms as well as population‐based norms and informal expectations regarding appropriate ages for the completion of education, marriage, or becoming a parent, and the sequencing and combination of these roles (Buchmann & Kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Yet, on aggregate well over half the youth population did not achieve the standard of a tertiary degree, which might also reflect high levels of drop-out, which are especially high in the US. The data thus suggest the need for viable alternative pathways for establishing oneself in the labour market, in addition to and above the academic track (Schoon, 2015).…”
Section: Educational Achievementmentioning
confidence: 93%
“…Yet, on aggregate well over half the youth population did not achieve the standard of a tertiary degree, which might also reflect high levels of drop-out, which are especially high in the US. The data thus suggest the need for viable alternative pathways for establishing oneself in the labour market, in addition to and above the academic track (Schoon, 2015).…”
Section: Educational Achievementmentioning
confidence: 93%
“…social roles since the late 1990s has been missing (Billari & Liefbroer, 2010, Schoon & Lyons-Amos, 2016. However, changes in employment and housing opportunities as well as patterns of family formation have likely led more recent generations to experience increasingly disaggregated pathways less well captured by past typologies (Schoon, 2015, Schoon & Lyons-Amos, 2016, 2017. This is particularly relevant for policymaking if young adults in pathways not captured in previous generations present heightened difficulties and would benefit from better-tailored policies (Finch, 2008, Crisp & Powell, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with the massive entry of women into the workforce and higher education, studies found that pathways became more similar between men and women towards the end of the 20th century (Winkler-Dworak & Toulemon, 2007;Ross et al, 2009). Few, however, have examined the extent to which this convergence included family life and housing transitions, and whether this has remained stable since the 1990s (Settersten et al, 2005;MacMillan & Copher, 2005;Amato et al, 2008;Oesterle et al, 2010;Schoon, 2015). Illustrating this in a US sample followed between the ages of 18 and 30, a study found two similar pathways for men and women yet key differences in a third "precarious" pathway, in which men were less likely to be working full-time whereas women were more likely to rapidly enter parenthood while unmarried (Oesterle et al, 2010).…”
Section: New Differences In Role Combinations By Gender and Social Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a great deal of research also makes it clear that the transition to adulthood is not uniform across different demographic and socioeconomic groups. Social class, gender, race/ethnicity, and immigrant status shape the pathways to adulthood, making some groups of young people more successful than others in the transition to adulthood (Gonzales and Roth, 2015;Sandefur et al, 2005;Schoon, 2015).…”
Section: Introductionmentioning
confidence: 99%